Teaching English at Junior High School: Post-Pandemic Recovery - Dian Saputra; Muhammad Nur Ashar Asnur; Rezkiah Hartanti; Melgasari Randa (Interference: Journal of Language, Literature, and Linguistics, 2023)
Abstract. The objective of this study is to determine the justifications for employing online and offline learning models in the covid-19 pandemic, as well as the barriers to their use. This study was carried out at SMP Negeri 2 Kota Sorong. This study employs a descriptive qualitative methodology. The data for the study were gathered via interviews. Principal, English teachers, and students of SMP Negeri 2 Kota Sorong were questioned during the interviews.  According to this study's findings, there were two learning models used during the covivirus-19 epidemic. Both online and traditional forms of education are included into the instructional format of this strategy. Because the students' financial resources are inadequate to support online learning, a school first used offline learning at the beginning of the Covid-19 pandemic. This is one of the reasons why the school employs both methods of education. In addition to the challenges students experience throughout the learning process, there are a further four obstacles. The conclusion findings indicated that the two learning models were though somewhat successful. Furthermore, the principal developed a new learning model for post-pandemic Covid-19 recovery. Keywords: Teaching, Learning Model, Obstacles.